Arrhythmias of children in the emergency department: incidence, management and outcome. (29th September 2015) - Clausen, H; Theophilos, T; Jachno, K; Babl, F
Abstract : Aims: Emergency department (ED) staff needs to establish accurate diagnosis and rapid management for children with arrhythmias. Limited data are available on the epidemiology of arrhythmias encountered in paediatric EDs. The authors aimed to characterise the incidence, management and outcomes of arrhythmias at a tertiary children's hospital. Methods: Retrospective review of medical records identified via the electronic ED database using ICD10 codes over a 6-year period (2002–2008). Patients less than 18 years were analysed using predefined criteria. Results: There were a total of 503 arrhythmias with an incidence of 140:100 000 ED presentations. Median age at presentation was 9.5 years (IQR 5.2–13.9) with 56% females. Supraventricular arrhythmias (SVT) represented the largest subgroup (n=267, 53%). Unspecified sinus arrhythmias were found in 153 cases followed by conduction disorders (n=37), cardiac arrest (n=20), ventricular tachycardia (n=19) and atrial flutter/fibrillation (AF) (n=7). Among children presenting in SVT, infants were far more likely to be admitted to hospital (81%) compared to older children (32%). 65 (13%) children had associated congenital heart disease and AF was more common in this subgroup. Defibrillators were used on only four occasions. 351 (67%) patients were discharged home, 138 (28%) were admitted of which 19 (4%) were admissions to intensive care. 15 (3%) children died in hospital. Conclusion: In this largest ED series in children, arrhythmias were infrequent, defibrillator use was very infrequent and observed mortality was low. These data will be important for staff education, resource allocation and to improve clinical guidance.